Real time implementation of a super twisting control of a BLDC motor - Ali Mousmi; Ahmed Abbou; Yassine El Houm; Anass Bakouri (Institute of Advanced Engineering and Science, 2019)
This paper presents and implements a Super-Twisting high order sliding mode control for a BLDC motor. Conventional sliding mode controller has a very fast response, it allows the convergence in finite time and characterized by its robustness against disturbances and uncertainties; However, the chattering phenomenon due to the discontinuous nature of its control organ degrades its performance, especially in case of mechanical membranes control. To overcome this disadvantage, the most commun solutions are based on the adaptation of its discontinuous nature at static regime, it reduces effectively the chattering phenomenon, but on the other hand impacts performance in terms of robustness. The Super-Twisting is an algorithm of high order sliding mode applicable on systems with relative degree 1, it produces a continuous control which cancels the chattering phenomenon and preserve all traditional sliding mode command performances. To validate the effectiveness and the robustness of the Super-Twisting controller for controlling brushless motors, experimental results using a 3KW BLDC motor are provided and compared with those of a conventional sliding mode controller.